THE INFLUENCE OF ENTREPRENEUR SPIRIT, MOTIVATION AND ORGANIZATIONAL CULTURE ON PERFORMANCE THROUGH THE COMPETENCY OF CIVIL SERVANTS IN TANJUNGPINANG CITY GOVERNMENT - Zulkifli Eko Purwanto; Chablullah Wibisono; Sajiyo; Indrayani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
In realizing the achievement of strategic programs, it is necessary to develop the competence of human resources, especially the state civil apparatus. Improving the quality of human resources representing change must not be stagnant, must be on par with the times or even develop beyond the skills and knowledge needed to run a modern government in the future. This means that competency development for state apparatus plays an important role in supporting organizational performance. The purpose of this study was to analyze the influence of the entrepreneurial spirit, motivation and organizational culture on performance through the competence of civil servants in the Government of Tanjungpinang City. Sampling in this study amounted to 150 samples. In this research, the sampling technique used is non-probability sampling with the technique taken is saturated sampling (census). The research method uses an associative method with a quantitative approach to the analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS program. The results of the research on the entrepreneurial spirit variable affect competence. Entrepreneurial spirit does not affect performance. Motivational variables affect competence. Motivational variables affect performance. Organizational culture variables affect competence. Organizational culture variables do not affect performance. Competency variables affect performance. While the indirect relationship Entrepreneurial spirit affects performance with competence as an intervening variable,